Islam and democracy: conflicts and congruence - Islam, Md Nazrul (2018)
Is authoritarianism intrinsic to Islam? Is Islam incompatible with democracy? These questions are frequently debated in the context of the study of the relationship between the Western and Islamic civilization. The debate has gained momentum since the last decade of the twentieth century, especially after the collapse of the former Soviet Union and the subsequent transition of socialist states in Eastern Europe and other authoritarian states in Asia and Latin America to democracy. The publication of The Clash of Civilizations by American scholar Samuel Huntington, in which he presented a controversial argument about a cultural divide and clash between the Islamic world and the West, pushed the debate even further. Apart from Muslim intellectuals, Western academics have spent a significant amount of time on these questions, with a multitude of articles and volumes examining the compatibility of Islam and democracy. In this paper, we will examine Islam’s relationship with democracy from normative and philosophical viewpoints, examining how the established values and principles of Islam as reflected in the Qur’anic and prophetic traditions correspond to Western democratic norms and practices. In order to obtain a profound understanding of this subject, we have delved into, through content analysis, the thoughts of several early modernist Islamic scholars who have had tremendous impact on contemporary Islamic revivalist movements throughout the world, and interviewed a number of contemporary Islamic thinkers in Bangladesh.